2003
DOI: 10.1124/jpet.102.042515
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Inhibits Lipopolysaccharide-Induced Tumor Necrosis Factor-α Production in an Intercellular Adhesion Molecule-1- and B7.1-Dependent Manner

Abstract: Lipopolysaccharide (LPS) is recognized as a key molecule in the pathogenesis of Gram negative sepsis and septic shock. In the present study, we demonstrate that LPS (1-1000 pg/ml) concentration dependently up-regulated the expression of intercellular adhesion molecule (ICAM)-1, B7.1, and B7.2 on human monocytes using fluorescence-activated cell sorting analysis, and that tumor necrosis factor (TNF)-␣ production induced by LPS in peripheral blood mononuclear cells (PBMCs) was inhibited by the addition of antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 38 publications
5
31
0
Order By: Relevance
“…As an example, in line with our observations, histamine via H2R, has been shown to inhibit the cytokine response to microbial products of monocytes [28,32] and dendritic cells [33]. Differentiation of monocytes into macrophages, on the other hand, induces the preferential expression of H1R over H2R [34], leading to increased production of IL-8 upon exposure to histamine [35].…”
Section: Discussionsupporting
confidence: 73%
“…As an example, in line with our observations, histamine via H2R, has been shown to inhibit the cytokine response to microbial products of monocytes [28,32] and dendritic cells [33]. Differentiation of monocytes into macrophages, on the other hand, induces the preferential expression of H1R over H2R [34], leading to increased production of IL-8 upon exposure to histamine [35].…”
Section: Discussionsupporting
confidence: 73%
“…10,[20][21][22] Using a panel of TLR ligands, we demonstrate that histamine exerts a diminished suppressive effect on cells from patients with IBD, possibly due to the decreased number of H 2 R + monocytes. The decrease in H 2 R + monocytes is negatively correlated with T H 17 cells in peripheral blood, which parallels the animal model data where increased IL-17 + lymphocytes were found in the mucosa of animals treated with a H 2 R antagonist or animals receiving H 2 Rdeficient lymphocytes.…”
Section: Discussionmentioning
confidence: 91%
“…The mechanism by which dibutyryl cAMP inhibits ICAM-1 may be due to inactivation of NF-B because the promoter region of the ICAM-1 genes contains binding sites for NF-B (49), and cAMP inhibits the activation of NF-B in a variety of human cells (26,50). In support of our results, Morichika et al (26) have recently demonstrated that dibutyryl cAMP in a concentration-dependent manner inhibited LPSinduced ICAM-1 expression on monocytes. These results indicate that the intracellular cAMP levels are a determinant of ICAM-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…One of the possible inflammatory responses that are associated with decreased cAMP levels is an increased expression of ICAM-1 (25,26). Further reasons to focus on ICAM-1 were the following: 1) ICAM-1 is found on both type I and type II alveolar epithelial cells (9,24,27); 2) LPS stimulation increases expression of ICAM-1 on type II cells in vitro (9,24,27); 3) the ligand for ICAM-1, i.e., Mac-1 (CD11a/CD18), is localized on leukocytes (28); and 4) ICAM-1 plays a central role in cell-cell contact-mediated immune responses (29) and the adherence of leukocytes to epithelial cells (27).…”
Section: Mediation Of Cell Cross Talk Through Icam-1 That Depends On mentioning
confidence: 99%